In vivo oxidative stress alters thiol redox status of peroxiredoxin 1 and 6 and impairs rat sperm quality - Liu, Yannan (Asian J Androl, 2017)
Oxidative stress, the imbalance between the production of reactive oxygen species (ROS) and antioxidant activity is a major culprit of male infertility. Peroxiredoxins (PRDXs) are major antioxidant enzymes of mammalian spermatozoa and are thiol oxidized and inactivated by ROS in a dose-dependent manner. Their deficiency and/or inactivation have been associated with men infertility. The aim of this study was to elucidate the impact of oxidative stress, generated by the in vivo tert-butyl hydroperoxide (tert-BHP) treatment on rat epididymal spermatozoa during their maturation process. Adult Sprague-Dawley males were treated with μmoles tert-BHP/kg or saline (control) per day intraperitoneal for 15 days. Lipid peroxidation (2-thibarbituric acid reactive substances assay), total amount and thiol oxidation of PRDXs along with the total amount of superoxide dismutase (SOD), motility and DNA oxidation (8-hydroxy-deoxyguanosine) were determined in epididymal spermatozoa. Total amount of PRDXs and catalase and thiol oxidation of PRDXs were determined in caput and cauda epididymis. While animals were not affected by treatment, their epididymal spermatozoa have decreased motility, increased levels of DNA oxidation and lipid peroxidation along with increased PRDXs (and not SOD) amounts. Moreover, sperm PRDXs were highly thiol oxidized. There was a differential regulation in the expression of PRDX1 and PRDX6 in the epididymis that suggests a segment-specific role for PRDXs. In conclusion, PRDXs are increased in epididymal spermatozoa in an attempt to fight against the oxidative stress generated by tert-BHP in the epididymis. These findings highlight the role of PRDXs in the protection of sperm function and DNA integrity during epididymal maturation.